Meningeal involvement in Wegener's granulomatosis confirmed and monitored by positive circulating antineutrophil cytoplasm in cerebrospinal fluid - Spranger, Matthias; Schwab, Stefan; Meinck, Hans-Michael; Tischendorf, Matthias; Sis, Jeanne; Breitbart, Andreas; Andrassy, Konrad (Neurology, 1997)
MRI and CSF investigations revealed meningeal involvement in a 29-year-old patient with biopsy-confirmed Wegener's granulomatosis. The intracranial manifestation of Wegener's granulomatosis was supported by the detection of pathologic circulating antineutrophil cytoplasm (c-ANCA) in the CSF. We monitored disease activity by c-ANCA measurement in the CSF. After repeated cycles of intrathecal administration of methotrexate and corticoids, progression of meningeal infiltration stopped, and CSF c-ANCA titers became negative. - NEUROLOGY 1997;48: 263-265
Gesehen am 02.11.2023